(untitled) (Eduscotech, 2023)
This study aims to enhance student activity and learning outcomes through the implementation of the STAD (Student Teams Achievement Divisions) cooperative learning model in the Social Studies (IPS) subject at SDN Suratmajan. The study adopts a Classroom Action Research (CAR) approach with two cycles, focusing on planning, execution, observation, and reflection stages. Data collection was done through observation, learning tests, and student activity questionnaires. The findings reveal a significant improvement in both student activity, particularly in group discussions, and academic performance across the cycles. The STAD model proved to be an effective strategy in enhancing student engagement and learning outcomes in IPS. The study recommends the broader application of the STAD model to improve the quality of education in elementary schools.